SCHOOLING DIVERSITY: NEWCOMER IMMIGRANT YOUTH, EDUCATION AND LEARNING SUPPORT IN JAPAN - Saki, Michi Ann (PEOPLE: International Journal of Social Sciences, 2018)
This initial research study briefly examined the experiences of ethnic minority youth and their families regarding their education in public schools in Kyoto, Japan, as well as the trends and challenges for both local governmental and non-governmental support organizations. This paper aims to further increase awareness about some of the experiences of ethnic diversity and accessibility of language support in Kyoto. This brief study aims to point out the trends of ethnic minority education, the current status of learning support services and the main reasons why the improvement of such support services for the new generation ethnic minority youth in Japan is urgently needed.